2020
DOI: 10.3390/ijms21103575
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Neuroprotective Effects Induced by Cannabidiol and Cannabigerol in Rat CTX-TNA2 Astrocytes and Isolated Cortexes

Abstract: Cannabidiol (CBD) and cannabigerol (CBG) are Cannabis sativa terpenophenols. Although CBD’s effectiveness against neurological diseases has already been demonstrated, nothing is known about CBG. Therefore, a comparison of the effects of these compounds was performed in two experimental models mimicking the oxidative stress and neurotoxicity occurring in neurological diseases. Rat astrocytes were exposed to hydrogen peroxide and cell viability, reactive oxygen species production and apoptosis occurrence were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 58 publications
0
31
1
1
Order By: Relevance
“…It is likely that these decreases in DNA damage proteins were caused indirectly, possibly because of the overall reductions in cellular damage and inflammation, as well as the known antioxidant properties of CBG that have both been demonstrated in other studies. 20,66 Nevertheless, direct modulation of these proteins should not be ruled out particularly as PPAR-c, a known target for phytocannabinoids, has been implicated in ATM signaling and the DDR. 67 Pretreatment with CBDV significantly increased expression of the majority of DNA damage proteins in astrocytes and exhibited a trend for increasing p21.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these decreases in DNA damage proteins were caused indirectly, possibly because of the overall reductions in cellular damage and inflammation, as well as the known antioxidant properties of CBG that have both been demonstrated in other studies. 20,66 Nevertheless, direct modulation of these proteins should not be ruled out particularly as PPAR-c, a known target for phytocannabinoids, has been implicated in ATM signaling and the DDR. 67 Pretreatment with CBDV significantly increased expression of the majority of DNA damage proteins in astrocytes and exhibited a trend for increasing p21.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the CBD-Keap1 adduct significantly contributes to Nrf2/ARE activation, which stimulates the antioxidant system. Proteomic analysis of its effect on cells also shows that CBD strongly activates the Nrf2/ARE pathway by interacting with the Nrf2 nuclear inhibitor Bach1 [ 10 , 50 ]. Changes in the structure of Bach1 reduce its possibility to compete with Nrf2 in DNA-binding, favoring the increased biosynthesis of cytoprotective proteins, including antioxidants [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In studies evaluating CBD effects in astrocytes, GFAP and S100β are the most commonly used astroglial markers. di Giacomo et al (2020) showed that astrocytes treated for 48 h with 1 μM of CBD present increased cell proliferation. The same concentration of CBD protected astrocytes from oxidative damage and apoptosis after exposure to hydrogen peroxide in vitro .…”
Section: Current Evidence Showing That Cbd Acts By Modulating Glial Cmentioning
confidence: 98%